Human Dignity as a Category pf Law - Wilczyński, Przemysław (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
The inherent and inalienable human dignity is treated by the legislator as an inviolable source of human and civil freedoms and rights, the respect and protection of which is the duty of public authorities. However, in the practice of creating and applying the law, human dignity understood in this way does not constitute a uniform category, which to a large extent seems to be caused by problems of a semantic nature. The article presents the issue of the legal category of human dignity in the Polish legal system. It reflects, among other things, on the philosophical foundation of human dignity and its inviolability. The article formulates a proposal to recognize the legal category of human dignity in two ways: as ontic dignity and as dignity recognized in a substantive legal manner.